Oral Administration of α-Asarone Promotes Functional Recovery in Rats With Spinal Cord Injury - Jo, Min-Jae; Kumar, Hemant; Joshi, Hari P.; Choi, Hyemin; Ko, Wan-Kyu; Kim, J. M.; Hwang, Sean S. S.; Park, Song Y.; Sohn, Seil; Bello, Alvin B.; Kim, Kyoung-Tae; Lee, Soo-Hong; et al. (Frontiers in Pharmacology, 2018)
α-Asarone, a bioactive compound found in Acorus plant species, has been shown to exhibit neuroprotective, anti-oxidative, anti-inflammatory and cognitive-enhancing effects. However, the effects of α-asarone on spinal cord injury (SCI) have not yet been elucidated. The present study investigated the effects of α-asarone on the mRNA of pro-inflammatory cytokines, macrophage polarization towards an anti-inflammatory M2 phenotype, and angiogenesis in rats with compressive SCI. α-Asarone was orally administered (10 mg/kg) once per day for 14 days following moderate static compression SCI. Compared to controls, α-asarone treatment significantly improved locomotor score, prevented neuroinflammation, and facilitated angiogenesis in the spinal cord at 14 days after SCI. Furthermore, α-asarone significantly reduced the TNF-α, IL-1β, IL-6, monocyte chemoattractant protein 1 (MCP-1), macrophage inflammatory protein 2 (MIP-2) and inducible nitric oxide synthase (iNOS) levels but increased the IL-4, IL-10, and arginase 1 levels at 24 hours after SCI. At 7 and 14 days after SCI, immunohistochemistry showed reduced reactive gliosis and neuroinflammation and an increased expression of M2 macrophage markers and angiogenesis. The results suggest that the inhibition of pro-inflammatory cytokines, macrophage polarization towards an anti-inflammatory M2 phenotype, and angiogenesis by α-asarone may be some of the mechanisms underlying the α-asarone-mediated neuroprotective effects on an injured spinal cord.